2006
DOI: 10.1103/physrevb.73.045435
|View full text |Cite
|
Sign up to set email alerts
|

Interwall interaction and elastic properties of carbon nanotubes

Abstract: The physical properties of a wide range of nonchiral single-walled carbon nanotubes (SWNT) and double-walled carbon nanotubes (DWNT) with nonchiral commensurate walls are studied. Equilibrium structures of SWNT and DWNT, as well as the interwall interaction energies of DWNT, are computed using a local density approximation within density functional theory with periodic boundary conditions and Gaussian-type orbitals. Based on ab initio structural characteristics, elastic properties of SWNT and DWNT are calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 56 publications
9
69
0
Order By: Relevance
“…A kink in the specific data around 225 K (indicated by arrow) may arise because of possible structural changes in these NTs. A prominent kink in the temperature‐dependent specific heat data for multi‐walled CNT around 60 K is interpreted as melting of orientational dislocations of individual tubes within multi‐wall NTs and also supported by theoretical models . In the absence of any reported phase transition of TiO 2 nanostructures around the observed temperature of 225 K, we propose a possible order–disorder phase transition in the TiO 2 NTs with wall thickness around 2–5 nm.…”
Section: Resultssupporting
confidence: 76%
“…A kink in the specific data around 225 K (indicated by arrow) may arise because of possible structural changes in these NTs. A prominent kink in the temperature‐dependent specific heat data for multi‐walled CNT around 60 K is interpreted as melting of orientational dislocations of individual tubes within multi‐wall NTs and also supported by theoretical models . In the absence of any reported phase transition of TiO 2 nanostructures around the observed temperature of 225 K, we propose a possible order–disorder phase transition in the TiO 2 NTs with wall thickness around 2–5 nm.…”
Section: Resultssupporting
confidence: 76%
“…27 If an accurate quantitative description of the interaction between the walls of carbon nanotubes (or layers of graphitic material) is available, the values for the barriers to their relative motion can be extracted from the interlayer interaction energy surfaces, and subsequently used to compute experimentally measurable quantities such as vibrational frequencies, 28 threshold and capillary forces, diffusion coefficients and mobilities. [29][30][31] In this paper, it is shown that the dispersion interactions are crucial in determination of the binding energies in layered materials, however they do not significantly affect the values of barriers to the relative motion of PAHs on hydrogenterminated graphene. Graphene, a single sheet of graphite, 32 represents an ideal viewing platform for molecular structures using transmission electron microscopy (TEM) because it provides a robust and low contrast support for molecules and other nanoscale species adsorbed on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic structure of DWNTs bundles has also been investigated by photoelectron spectroscopy, [28] revealing van der Waals interactions between the tubes in a bundle. Many theoretical studies have also been performed recently, [26,[29][30][31][32][33][34][35][36][37][38] confirming the presence of an interwall interaction and investigating its effect on the electronic structure, [30,35,36] the transport properties [32] and the mechanical properties [37,38] of double-walled nanotubes. In this paper, we report the study of the structural and electronic properties of double-walled carbon nanotubes deposited on a gold substrate using both STM and STS.…”
mentioning
confidence: 98%